Investigating the Implementation of Kahoot for Young Learners in Remote Learning Context - Ulandari, Sang Ayu Komang Yuli; Artini, Luh Putu; Myartawan, I Putu Ngurah Wage (Jurnal Pendidikan Bahasa Inggris undiksha, 2022)
The pandemic of COVID-19 has led to remote learning which requires teachers to be creative in presenting and delivering the learning materials. Online learning platforms are needed to connect students and retain their attention and motivation in learning, whereas the choice of the platforms is strongly tied to the teachers’ perception. Therefore, this study aimed to analyse the use of Kahoot for young learners and the teacher’ perception towards its implementation in remote learning context. It was because Kahoot was reported to have a significant and direct positive effect on the students’ learning outcomes and studies related to its use for young learners were still limited. This was a qualitative study that was conducted by taking an English teacher as a subject. The data were collected through observation, interview, and questionnaire. The results showed that the implementation of Kahoot for young learners was carried out synchronously in two sessions with two different materials for one meeting. The first session was used for academic quiz while the second session was intented for fun activity, discussing general knowledge about the world, such as asking about the name of the character in a cartoon, answering riddles, and so on. The results also indicated that the teacher also had positive perception towards the implementation of Kahoot in remote learning.